Statistical analysis of customer satisfaction of tv goods in foreign markets: (special case at a brand level in russian market) - Guluzade, Elkhan (My University, 2007)
YABANCI PAZARLARDA TV ÜRÜNLERİNİN MÜŞTERİ MEMNUNiYETİNİN İSTATİSTİKSEL ANALİZİ (RUSYA PAZARINDA MARKA SEVİYESİNDE ÖZEL ÇALIŞMA) Tarih boyunca, ihracat sektörü dünya ülkeleri ekonomisinde önemli röl oynamıştır. Ülkeler yatırımların yapılmasına, sanayinin büyümesine be buradan ihracat rakamlarının yükselmesine özel dikkat yetiriyorlar; bunun sonucu olarak ülkeye yabancı para akışı artıyor ve hayat standartları yükseliyor. Bu çalışma Türk elektrik – elektronik sektörüne ve bu sektörün ihracatına odaklanmıştır. Bu sektörün verilerinin tam analizinden sonra, TV ürünlerinin Türk elektrik – elektronik sektörü ihracatında önemli röle sahip olduğu anlaşılmıştır. Daha sonra, rakamlardan Vestel Dış Ticaret AŞ”nin Türk TV ihracatına büyük katkısı olduğu ve Rusya pazarının Vestel”in en büyük potansiyel pazarlarından biri olduğu ortaya çıkmıştır. Çalışmanın amacı, Vestel TV”nin Rusya pazarındakı satışlarını ve Vestel TV ürünlerinin Rusya”dakı müşteri memnuniyetini analiz etmek; ve müşteri memnuniyetini etkileyen faktörleri ortaya çıkarmaktır. Araştırma (anket) verileri tamamlandıktan sonra, bu veriler farklı istatistiksel yöntemlerle bilgisayar programlarını kullanarak tahlil edilmiştir. Genel memnuniyet ve etkenler arasındakı bağ ve ilişkiler araştırılmış, ilgisiz etkenler modelden çıkarılmış ve müşteri memnuniyetini gerçekten etkileyen faktörler araştırma modelinde kalmıştır.

STATISTICAL ANALYSIS OF CUSTOMER SATISFACTION OF TV GOODS IN FOREIGN MARKETS (SPECIAL CASE AT A BRAND LEVEL IN RUSSIAN MARKET) Throughout the history, the exports sector has been played a significant role in the economy of world countries. The countries pay special attention to investments, enlargement of manufacture industry and hence the enhancement of exports; which will bring to attracting foreign money to country and increase life standards. The given study is focused on the Turkish electronics sector and the exports of this sector. After the thorough analysis of this sector’s data, it is found that, the TV goods have a significant role in Turkish electronics sector exports. Then, we found that, Vestel foreign trade co. has the highest contribution to Turkish TV exports and Russian market is one of the most potential markets of Vestel Company. Further, it is aimed to analyze the sales of Vestel TVs in Russian market and the level of Customer Satisfaction in Vestel TV goods in Russia; and to determine the factors affecting the customer satisfaction. After the completion of the survey data, these data were analyzed with different statistical methods by using software. It is tried to investigate the relationships between the factors and overall satisfaction; the unrelated factors were eliminated and the factors which are really affect the customer satisfaction were stayed in the research model.
Keywords: Elektrik; Elektronik_İhracat; İstatistik; Müşteri Memnuniyeti